TRANSAKSI vALAS (FOREX EXCHaNGE) SECARA ONLINE STUDy ANALISIS MENURUT PERSPEKTIF ISLAM - Abdul Hamid (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2016)
Abstract. Forex is the most liquid market and the biggest one in the world operating for 24 hours, moving from one zone to another one within variety of world financial centers. The velocity of money in the Forex market reached about 3.8 trillion USD per day. In general, many Muslims society in the world and in Indonesia in particular, engage in online Foreign Exchange trading, although most of them do not realize at all about the validity of buying and selling practice based on Sharia perspective. This paper attempts to analyze the practice of trading or selling foreign currency online to guarantee the profits generated from this practice in accordance with Sharia. This is due to trade or exchange must be conducted carefully to avoid the chances of riba al-Buyu’ which is forbidden by Sharia based on the hadith of the Prophet S.A.W related to 6 items of riba transactions. Keywords: Forex, online and al-Buyu’